Deconstructing Discourses in Assessments of Child Neglect. (12th March 2021) - Casey, B; Hackett, S
Abstract: This article presents the findings of a qualitative study exploring how child neglect is 'performed' in social work practice. Informed by Foucauldian and feminist theoretical positions, semi-structured interviews were conducted with ten local authority social workers, eight Children's Centre professionals in England and eight parents who had received professional intervention due to concerns about child neglect. In addition, ten case files were analysed where child neglect was a substantive concern. This article explores the discourses that were produced in social workers' assessments of child neglect. In a neo-liberal context in which cuts are being made to childcare services, professionals were preoccupied with the identification and management of neglectful families by risk. Professional debates surrounding contested thresholds into services and categorisation of neglectful families are explored. Judgements of 'good enough' mothering as well as bureaucratic and managerial constraints to holistic, analytical and quality assessments are identified. The article also explores the bureaucratic performance of children's assessed identities through which children become the objects of the assessment rather than active subjects. The article concludes with recommendations for practice and future research.